2018
DOI: 10.1016/j.micromeso.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigations in pure-silica and Al-ZSM-12 with MTEA or TEA cations

Abstract: Two different quaternary ammonium cations, methyltriethyl-(MTEA) and tetraethylammonium cations (TEA) were used as templates in the synthesis of puresilica as well as aluminosilicate ZSM-12 (MTW-type) frameworks. The distribution of the template cations in the 12MR channels in the 1-dimensional framework topology was studied; thus the as-prepared products were characterized by means of X-ray powder diffraction, Raman, transmission FTIR, solid-state NMR spectroscopy, thermogravimetric and elemental analyses and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…However, their samples have different chemical compositions than those synthesized in our study. Results similar to those obtained in our study were reported in [25] even for samples of different chemical composition and obtained with others crystallization time. The analysis of the TG curves of the samples of Sn-ZSM-12 containing different tin concentrations indicated that the addition of tin occasioned reduction in the total mass loss (Table I) probably due to the increase in structural defects caused by the incorporation of tin in the structure.…”
Section: Resultssupporting
confidence: 93%
“…However, their samples have different chemical compositions than those synthesized in our study. Results similar to those obtained in our study were reported in [25] even for samples of different chemical composition and obtained with others crystallization time. The analysis of the TG curves of the samples of Sn-ZSM-12 containing different tin concentrations indicated that the addition of tin occasioned reduction in the total mass loss (Table I) probably due to the increase in structural defects caused by the incorporation of tin in the structure.…”
Section: Resultssupporting
confidence: 93%
“…ZSM-12 is usually synthesized from quaternary ammonium salts, which are involved in the formation of the aluminosilicate porous structure and affect the characteristics of the resulting material. Thus, a significant number of reports have focused on the study of nucleation and growth of crystals of this zeolite in the presence of various organic ammonium salts, such as methyltriethylammonium and N,N-dimethyl-N-ethyl(monoethanol)ammonium (Kulikov et al, 2019), tetraethylammonium (Toktarev & Ione, 1997;Kasunič et al, 2009), trimethylethylammonium (Počkaj et al, 2018), imidazole, pyridine and piperidine salts (Kore, R. & Srivastava, 2012), and diquaternary ammonium salts (Moini et al;1994;Han et al, 2005;Veselý et al, 2019).…”
Section: Introductionmentioning
confidence: 99%